(untitled) (Computer systems and information technologies, 2021)
When software is developed, it is assumed that it can be used by different groups of users. The difference between these groups may be not only in the level of technical qualifications, but also in physiological and psychological differences, features of hardware, software, environment, and so on. Lead to the need of creation of the universal interface that can suit all users. Due to the fact that all users are different, this problem has no solution and in fact the interface corresponds to the property "least inconvenient" instead of "most convenient". The problem of adapting software and hardware to the conditions of use is solved by each team of developers with their own methods, but the approach to analyzing the problem and solutions is almost the same and comes down to building scenarios for the use of hardware and software. The article represent a general approach to the creation of multi-scenario systems for various purposes - electronic educational systems, hardware educational systems for the visually impaired, medical diagnostic systems. The following problems of development were solved in the article: adaptive intelligent interface, architecture and structure of adaptive intelligent interface and algorithms of functioning of adaptive system interface agents. The presented examples of hardware and software solutions, and the visualization of the model of the adaptive learning system will allow to develop own algorithms for the implementation of multi-scenario systems.